Planting System cum High Density Planting in Guava (Psidium guajava L.) Growth Yield and Quality of cv. Sardar in Kymore Plateau of Madhya Pradesh - Singh, T. K.; Kumar, Prashant; Singh, Divya; Bose, U. S.; Prajapati, Sunil (International Journal of Bio-resource and Stress Management, 2020)
The present experiment was carried out at Fruit Research Station, Kuthulia, College of Agriculture, Rewa, Madhya Pradesh, India during the year 2005-06 to 2014-15. The results revealed that various planting system exhibited significant effect on growth, yield and quality parameters of Guava. The maximum tree heights were recorded (5.17 m) and highest canopy height (4.57 m) in double hedge row system. The maximum girth of root stock (60.43 cm) and girth of scion were recorded (48.56 cm) in square system of planting. Significantly maximum tree spread (mean of E-W and N-S) was recorded (E-W 10.26 m and N-S 10.20 m)fallowed by (N-S 6.70 m and E-W 6.49 m).The maximum yield (397.07 ha-1) was estimated in double hedge row system followed by (339.7 ha-1) in cluster planting system. The physico-chemical properties of fruits maximum length of fruit (6.46 cm) and width of fruit (6.96 cm) were recorded in double hedge row system. The maximum flesh percentage (97.89%) in square system. The seed percent (2.72%) in hedge row system. The minimum test weight (1.18 g) was found in hedge row system. The maximum TSS (12.40 °B) in square system. The maximum reducing sugar (5.10%) and the maximum non-reducing sugar (7.30%) in square system. The maximum acidity (0.39) was recorded in hedge row system.